Mechanism of Radix Bupleuri and Hedysarum Multijugum Maxim drug pairs on liver fibrosis based on network pharmacology, bioinformatics and molecular dynamics simulation - Lefei Yu; Pan Yu; Yongchang Cao; Weiya Cao (PLoS ONE, 2025)
A number of studies demonstrate the therapeutic effectiveness of Radix Bupleuri (RB) and Hedysarum Multijugum Maxim (HMM) in treating liver fibrosis, but the exact molecular mechanisms remain unclear. This study aims to explore the mechanism of RB-HMM drug pairs in treating liver fibrosis by using network pharmacology, bioinformatics, molecular docking, molecular dynamics simulation technology and in vitro experiments. Totally, 155 intersection targets between RB-HMM and liver fibrosis were identified. In the protein-protein interaction (PPI) network, the top 10 hub targets with the highest node connection values were TNF, IL-6, AKT1, EGFR, HIF1A, PPARG, CASP3, SRC, MMP9 and HSP90AA1. GO functional and KEGG pathway enrichment analysis involved 335 biological processes, 39 cellular components, 78 molecular functions, and 139 signaling pathways. The bioinformatics analysis indicated that TNF, IL-6, PPARG and MMP9 were promising candidate genes that can serve as diagnostic and prognostic biomarkers for liver fibrosis. Moreover, the molecular docking and molecular dynamic simulation of 50 ns well complemented the binding affinity and strong stability between the three common compounds MOL000098 (quercetin), MOL000354 (isorhamnetin) and MOL000422 (kaempferol) and four final hub targets (TNF, IL-6, PPARG and MMP9). Calculation of binding free energy and decomposition free energy using MM_PBSA and MM_GBSA also validated the strong binding affinity and stability of 12 systems. MOL000098 (quercetin) was selected via MTT assay and western blot assay verified MOL000098 (quercetin) treatments remarkably decreased the protein levels of TNF and IL-6 in TGFβ stimulated LX2 cells. In conclusion, RB-HMM drug pairs can affect the progression of liver fibrosis through multiple components, multiple targets and multiple pathways, and treat liver fibrosis possibly through anti-inflammatory and affecting cell apoptosis.